Deepening of Pension Reforms and Improvement of Investment Activities of Transition Economies - Zakirkhodjaeva Sh. A. (Research Parks Publishers, 2022)
In this article said about deepening of pension system reforms and development of investment activities in transition economies, also there are conclusions and suggestions related to current pension system reforms of transition economies and deepening of these reforms as well as development of investment activities.